Marketing patterns of agricultural commodities in an upland area of Central Java - Caroline M. van Ommeren; Jan G.L. Palte (Indonesian Journal of Geography, 1986)
In the uplands of Central Java a wide variety of dry cultivated crops are produced for subsistence as well as for cash. The marketing channels for these crops are also diverse. The producers can choose between selling at the market place or at their farms; either to consumers or traders; or they can sell their products to wholesalers in the towns. However, this freedom of choice is not absolute and is determined by the quantity of the merchandise. Farmers/who can sell large amounts of produce are able to bypass some steps in the hierarchical order of market places or traders. Thus, producers with relatively large farmlands can sell their commodities in more profitable ways compared to those with /smaller farms. Moreover, the latter are often forced to sell their produce below market value to traders who provided them with advance or who bought the crop before harvest (tebasan), because of their need for cash